Aurora A mediates cross-talk between N- and C-terminal post-translational modifications of p53 - Warnock, Lorna Jane (Landes Bioscience, 2011)
The serine/threonine protein kinase Aurora A is known to interact with and phosphorylate tumor suppressor p53 at Serine 215 (S215), inhibiting the transcriptional activity of p53. We show that Aurora A positively regulates human p53 protein levels and, using isogenic p53 wild-type and p53-null colorectal carcinoma cells, further show that p53 regulates human Aurora A protein expression. S215 is located in the DNA-binding core of p53 and at the center of the cryptic epitope for PAb240 antibody, which is used to detect mutant and denatured p53. Following denaturing SDS PAGE, the PAb240 epitope was detectable by immunoblotting in only two out of eight cell lines. The efficacy of novel p53-targeted anticancer therapies may be influenced by the conformational state of p53, therefore, the initial determination of p53 status may be relevant. We found no correlation between phosphorylation of p53 at S215 and PAb240 antibody recognition. However, phosphorylation at S37 was positively associated with PAb240 reactivity. More importantly, we provide the first evidence of Aurora A-mediated cross-talk between N- and C-terminal p53 post-translational modifications. As p53 and Aurora A are targets for anticancer therapy the impact of their reciprocal relationship and Aurora A-induced post-translational modification of p53 should be considered.